Analysis of Halal and Marketing Strategy for Broiler Chickens' Supply Chain during Covid-19 : A Case Study in Yogyakarta, Indonesia - Hayati Mukti Asih; Fahri Firmansyah; Muhammad Faishal (TEKNIK, 2021)
Corona virus has a destructive impact on the world's economy, especially in Indonesia, making a large-scale social restriction policy (SRL). Many restaurants, hotels, schools, and colleges in Yogyakarta are closed. Consumers, mostly students from outside Yogyakarta, have to return to their hometowns. This case impacts the decline in chicken prices to cover losses due to excess supply and decreasing demand. This research aims to analyze the decline in chicken prices, halal products' and the concept of marketing strategies impact on the chicken supply chain during the Covid-19 outbreak in Yogyakarta. This research used SEM to obtain accurate analysis and descriptive results to overview phenomena from society under study. The analysis using SEM shows that halal factors do not significantly affect consumer decisions in buying chicken. However, it was found that there was an increase in consumers in online shopping, which could create new strategies in marketing strategies. The application of online marketing strategies will improve consumers' services so that it is expected to be a novel value that can increase consumer buying interest during the Covid-19 outbreak in Yogyakarta, Indonesia.